SPATIAL ANALYSE OF HUMAN CASES OF VISCERAL LEISHMANIASIS IN THE STATE OF PERNAMBUCO, BRAZIL: SPATIAL ANALYSE OF HUMAN CASES OF VISCERAL LEISHMANIASIS IN THE STATE OF PERNAMBUCO, BRAZIL - Leite, Cicero Emanoel Alves; Vidal, Suely Arruda; Quental, Oilma Barros de (Brazilian Journal of Production Engineering, 2020)
Visceral leishmaniasis is an important public health problem in the world, especially in Brazil, with 96% of cases in the Americas. The main objective of this study was to analyze the spatial distribution of human cases of visceral Lishmaniosis in the State of Pernambuco, Brazil. Descriptive study of a historical series (2005 to 2014) using databases of notifiable diseases information (SINAN) and on mortality (SIM) systems of cases of visceral leishmaniasis (CID-10 B550). For the analysis, it used the software Epi Info v. 7.1.5 in which, from the Georeferencing of cases of visceral leishmaniasis, cartographic maps were generated with geographic limits of the municipalities and classified according to the number of cases and the macro-region of health. The sample consisted of 954 cases reported in the study period that presented distribution in 70% of the municipalities of Pernambuco, which had at least one case of the disease. Four municipalities (Caruaru, Ouricuri, Petrolina and Salgueiro) presented cases in all the historical series studied. Almost half of the cases in Pernambuco (48.5%) were concentrated in the IV health macro-region, where 100% of their municipalities have cases of the disease. The study concluded that the geographical distribution of cases of visceral leishmaniasis covered almost all states during the historical series, with a higher burden in the IV macro-region.
Keywords: Visceral leishmaniasis; Epidemiology; Spatial analysis; Geographic information systems